2014
DOI: 10.1002/hep.26892
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral treatment for hepatitis C virus infection is associated with improved renal and cardiovascular outcomes in diabetic patients

Abstract: Hepatitis C virus (HCV) infection is causally associated with insulin resistance and diabetes mellitus. This population-based cohort study aimed to investigate whether antiviral therapy for HCV infection was associated with improved clinical outcomes related to diabetes. From the Taiwan National Health Insurance Research Database, 2,267,270 Taiwanese residents diagnosed with diabetes mellitus were screened for eligibility. HCV infection was defined by a specific diagnosis code and measurement of serum antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
248
3
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(268 citation statements)
references
References 38 publications
15
248
3
2
Order By: Relevance
“…(1) For example, elevated rates of psychiatric and physical comorbidity as well as polypharmacy in this population put disabled HCV patients at risk of possible drug-drug interactions even while on interferon-free therapy. Furthermore, although findings show that clearing the virus with interferon-based therapy may reduce the incidence of some extrahepatic manifestations of HCV, (5) in our work we have detected no effect of interferon therapy of 24 weeks at reducing metabolic and vascular risk over a followup period of 2 years. This could likely be due to impaired effectiveness of interferon-based therapy at achieving viral clearance in this vulnerable population.…”
Section: To the Editorcontrasting
confidence: 83%
“…(1) For example, elevated rates of psychiatric and physical comorbidity as well as polypharmacy in this population put disabled HCV patients at risk of possible drug-drug interactions even while on interferon-free therapy. Furthermore, although findings show that clearing the virus with interferon-based therapy may reduce the incidence of some extrahepatic manifestations of HCV, (5) in our work we have detected no effect of interferon therapy of 24 weeks at reducing metabolic and vascular risk over a followup period of 2 years. This could likely be due to impaired effectiveness of interferon-based therapy at achieving viral clearance in this vulnerable population.…”
Section: To the Editorcontrasting
confidence: 83%
“…In a unique and large natural history study, Lee et al showed that patients with chronic HCV infection had a cumulative non-liver-related mortality rate of 19.8% after 18 years of follow-up, which was considerably higher as compared to those patients who cleared their HCV infection (11.0%) and those who never encountered HCV (12.2%) (2). Although not as extensively as for the cirrhosis-related complications, data are slowly emerging that achievement of SVR is also associated with a reduced occurrence of solid extra-hepatic clinical endpoints such as renal failure and cardiovascular events (3,4). These potential clinical benefits may explain the reduced occurrence of death due to extrahepatic causes in case of SVR, which Tada et al describe here.…”
Section: See Article On Page 817mentioning
confidence: 71%
“…Additionally, viral eradication has been shown to ameliorate insulin resistance, atenuating the risk of new-onset T2DM [41]. Update on Hepatitis CSeveral observational studies indicated that eradication of HCV with interferon (IFN) and ribavirin (RBV) is associated with improved insulin sensitivity [42][43][44].…”
Section: Treatment Of Insulin Resistance and Diabetes With The Eradicmentioning
confidence: 99%
“…The clinical impact of successful antiviral therapy on the long-term outcome of T2DM in diabetics with CHC is still unknown, mainly because of the lack in proper prospective studies although data from population-based research in Taiwan reported improved renal and cardiovascular outcomes in diabetic patients treated with antiviral HCV treatment [41].…”
Section: Treatment Of Insulin Resistance and Diabetes With The Eradicmentioning
confidence: 99%